Corruption, types of corruption and firm financial performance: New evidence from a transitional economy - Vũ, Văn Hưởng (Springer, 2022)
Using a nationwide survey of provincial institutional quality and a sample of private manufacturing small and medium scale enterprises (the SMEs), this paper contributes to the literature by considering for the first time the effects of corruption on the financial performance of Vietnamese private SMEs. Interestingly, contrary to previous findings, we find that corruption when measured by a dummy variable, does not affect firms’ financial performance after controlling for heterogeneity, simultaneity and dynamic endogeneity. However, the intensity of bribery and the majority of the forms of corruption were found to have negative impacts on firms’ financial performance. Hence, a typical approach using only a dummy variable for bribery might not adequately evaluate the impact of bribe intensity or even ignores the negative impacts of some types of bribes on firms’ financial performance. The findings suggest that anti-corruption measures are vital for the development of the Vietnamese private SMEs.